2019
DOI: 10.1155/2019/5948686
|View full text |Cite
|
Sign up to set email alerts
|

Microglial BDNF, PI3K, and p-ERK in the Spinal Cord Are Suppressed by Pulsed Radiofrequency on Dorsal Root Ganglion to Ease SNI-Induced Neuropathic Pain in Rats

Abstract: Background. Pulsed radiofrequency (PRF) on the dorsal root ganglion (DRG) has been applied to alleviate neuropathic pain effectively, yet the mechanisms underlying pain reduction owing to this treatment are not clarified completely. The activated microglia, brain-derived neurotrophic factor (BDNF), phosphatidylinositol 3-kinase (PI3K), and phosphorylated extracellular signal-regulated kinase (p-ERK) in the spinal cord were demonstrated to be involved in developing neuropathic pain. Also, it has been just known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 50 publications
1
26
1
Order By: Relevance
“…In this study, differences in gene expression for the PI3Kγ-AKT-cGMP-JNK signaling pathway (Xu et al, 2019) and morphine tolerance (Chen et al, 2018;König et al, 2010).…”
Section: Discussionmentioning
confidence: 72%
“…In this study, differences in gene expression for the PI3Kγ-AKT-cGMP-JNK signaling pathway (Xu et al, 2019) and morphine tolerance (Chen et al, 2018;König et al, 2010).…”
Section: Discussionmentioning
confidence: 72%
“…ERK and NF-κB p65 signaling pathways were activated after sciatic nerve injury, with increased protein expression, which are associated with spinal glial activation and central sensitization [25][26][27]. The double immunofluorescence labeling for c-fos and p-ERK was increased after the saphenous nerve injury and disconnection from their dominant receptive field, suggesting that the collateral synaptic input to second-order spinal dorsal horn neurons was activated [52].…”
Section: Discussionmentioning
confidence: 98%
“…However, it is not clear whether there is a therapeutic effect of NCSCs on central sensitization in the spinal cord that leads to pain relief and improved outcomes after sciatic nerve transection (SNT). While intraspinal injection of BMSCs was reported to suppress the NF-κB and p-p38 MAPK pathways in the spinal cord after spinal cord injury (SCI) [24], it is still unknown whether the ERK and NF-κB signals, which are associated with spinal glial activation and central sensitization [25][26][27], are associated with the effect of peripherally applied NCSCs. The relevant underlying mechanisms remain unelucidated.…”
mentioning
confidence: 99%
“…In the SNI rat model, it was found that PRF could relieve neuropathic pain by inhibiting the overexpression of IRF8 and BDNF in the spinal cord of NAC, 24 and inhibiting the activation of spinal microglia to downregulate DNF and the phosphorylation of PI3K and ERK. 25 While in the CCI rat model, it was found that PRF can upregulate the transcription and translation of GDNF in the compressed sciatic nerve, 26 inhibit the activity of IRF8, p38 and microglia in the spinal cord of rats, 27 downregulate the expression of chain proteins, 28 and enhance the levels of interleukin-1 (IL-1) and tumor necrosis factor (TNF) in the blood of rats, 28 and then achieve the purpose of relieving neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%